2005
DOI: 10.1016/j.molcel.2005.10.021
|View full text |Cite
|
Sign up to set email alerts
|

p38-Dependent Phosphorylation of the mRNA Decay-Promoting Factor KSRP Controls the Stability of Select Myogenic Transcripts

Abstract: Transcriptional and posttranscriptional processes regulate expression of genetic networks in response to environmental cues. The extracellular signal-activated p38 MAP kinase (p38) pathway plays a fundamental role in conversion of myoblasts to differentiated myocytes. p38 phosphorylates specific transcription factors and chromatin-associated proteins promoting assembly of the myogenic transcriptome. Here, we demonstrate that p38 alpha and beta isoforms also control muscle-gene expression posttranscriptionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
260
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(271 citation statements)
references
References 34 publications
9
260
1
1
Order By: Relevance
“…, lanes 9-12), respectively. Internally 32 P-labeled, pri-miR-206 RNA substrate was added and its processing monitored as described by Briata et al 8 Statistical significance: **Po0.01 (Student's t-test) PI3K/AKT inhibits KSRP ability to promote decay of myogenin mRNA while promotes its recruitment to myogenic miRNA processing complexes. We and others have shown that stabilization of inherently labile muscle specific transcripts takes place during C2C12 cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…, lanes 9-12), respectively. Internally 32 P-labeled, pri-miR-206 RNA substrate was added and its processing monitored as described by Briata et al 8 Statistical significance: **Po0.01 (Student's t-test) PI3K/AKT inhibits KSRP ability to promote decay of myogenin mRNA while promotes its recruitment to myogenic miRNA processing complexes. We and others have shown that stabilization of inherently labile muscle specific transcripts takes place during C2C12 cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that stabilization of inherently labile muscle specific transcripts takes place during C2C12 cell differentiation. [6][7][8] Myogenin and p21 mRNAs are unstable in C2C12 myoblasts cultured in GM and KSRP is required for their decay while MAPK p38-induced inactivation of KSRP (which occurs in differentiating myoblasts) contributes to myogenin and p21 induction. 8 Figure 5a and Supplementary Figure S6a show that AKT increased the half life of myogenin and p21 mRNAs when activated in C2C12 myoblasts cultured in GM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The function of p38 during myogenesis is complex, with activation of p38 during the myogenic process recruiting the SWI-SNF chromatin remodeling complexes to specific myogenic loci [19] as well as modifying gene expression posttranscriptionally via p38-mediated regulation of myogenic mRNA stability [20]. p38 increases myogenic regulatory factor (MRF) activity via phosphorylation of MEF2 [21] and E proteins, promoting heterodimerization of MRFs such as MyoD with E47.…”
Section: Introductionmentioning
confidence: 99%